Characteristics of Edible Films Based on Corn Starch and Protein Isolates from Liquid Waste Extraction of Tofu Processing Industry - Rina Mirdayanti; Amalia Amalia (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
One factor contributing to the environment's waste is industrial activity both large and small scale. During this time, the waste collection is done by dumping it into a ditch and flowing it into the river, thus worsening environmental sanitation. This study aims to analyze the character of edible films of corn starch with protein isolates from the extraction of tofu processing industry wastewater. Samples were analyzed to determine the tensile strength and elongation of the resulting film by varying the amount of protein isolates, 0%, 3%, 5%, 7% and 9%. The protein extraction process was carried out by centrifugation, while the water vapor transmission test was by the saucer method, while the identification of functional groups was through FTIR analysis. The results showed that the highest mechanical properties were obtained in the variation of 5% protein isolates with a value of 52.16 MPa and elongation of 38.4%. For water vapor transmission rate (WVTR), film comparisons were made with 5% variation of protein isolates and 0% protein isolates. Films with 5% protein isolates have a smaller water absorption of 0.56%, than films with 0% of 0.66%. The value of water vapor transmission rate shows a very significant ratio, at 5% protein isolate of water vapor transmission at 0.00176 g/m2/day, much smaller than 0% protein isolate at 0.00864 g/m2/day. IR spectra showed the presence of amide groups I and II on the results of the analysis of protein isolates. While the globular structure of proteins is shown by the absorption of wave numbers 1667 and 1650 cm-1.